Does the surface conditioning of glass and hybrid ceramics with self-etching silane present a bond strength similar to that of conventional bonding? Systematic review and meta-analysis of in vitro studies - Bento, Victor Augusto Alves [UNESP]; de Souza Rolim, Pedro Antônio [UNESP]; de Matos, José Roberto Vergínio [UNESP]; de Araújo Lemos, Cleidiel Aparecido; Pellizzer, Eduardo Piza [UNESP]; Guiotti, Aimée Maria [UNESP] (Wiley, 2024)
Purpose: To evaluate, through in vitro studies, the bond strength of vitreous and hybrid ceramics with self-etching surface treatment compared to conventional treatment. Methods: This systematic review followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) and was registered on the open science framework (OSF) platform for in vitro studies. A population, intervention, control, and outcome (PICO) question was formulated: “Does the surface conditioning of glass and hybrid ceramics with self-etching silane present a bond strength similar to that of conventional bonding?”. A literature search was carried out in the PubMed, Embase, Web of Science, Cochrane Library, and ProQuest databases until September 2023. The Joanna Briggs Institute (JBI) critical appraisal guidelines for quasi-experimental studies were used for risk assessment of bias. The meta-analysis was based on the inverse variance (IV) method (p < 0.05). Results: A total of 29 in vitro studies published between 2017 and 2022 were included in this systematic review, totaling 1889 ceramic samples. The meta-analysis indicated a significant decrease in the bond strength of HF 4%–5% with silane compared to self-etching (p < 0.05; MD: 0.34; 95% CI: 0.13–0.35; I2 = 3%, p = 0.42), while it indicated that there was no significant difference between self-etching compared to 9%–10% HF with silane (p = 0.92; MD: 0.02; 95% CI: −0.32 to 0.36; I2 = 14%, p = 0.32). Conclusion: Self-etching primer presents bond strength that is superior to or similar to conventional surface treatment on glass and hybrid ceramics.
Keywords: bond strength; CAD–CAM; ceramics; resin–ceramics; self-etching